The thromboxane receptor antagonist NTP42 promotes beneficial adaptation and preserves cardiac function in experimental models of right heart overload - Mulvaney, Eamon P.; Renzo, Fabiana; Adão, Rui; Dupre, Emilie; Bialesova, Lucia; Salvatore, Viviana; Reid, Helen M.; Conceição, Glória; Grynblat, Julien; Llucià-Valldeperas, Aida; Michel, Jean-Baptiste; Brás-Silva, Carmen; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Pulmonary arterial hypertension (PAH) is a progressive disease characterized by increased pulmonary artery pressure leading to right ventricular (RV) failure. While current PAH therapies improve patient outlook, they show limited benefit in attenuating RV dysfunction. Recent investigations demonstrated that the thromboxane (TX) A2 receptor (TP) antagonist NTP42 attenuates experimental PAH across key hemodynamic parameters in the lungs and heart. This study aimed to validate the efficacy of NTP42:KVA4, a novel oral formulation of NTP42 in clinical development, in preclinical models of PAH while also, critically, investigating its direct effects on RV dysfunction. Methods The effects of NTP42:KVA4 were evaluated in the monocrotaline (MCT) and pulmonary artery banding (PAB) models of PAH and RV dysfunction, respectively, and when compared with leading standard-of-care (SOC) PAH drugs. In addition, the expression of the TP, the target for NTP42, was investigated in cardiac tissue from several other related disease models, and from subjects with PAH and dilated cardiomyopathy (DCM). Results In the MCT-PAH model, NTP42:KVA4 alleviated disease-induced changes in cardiopulmonary hemodynamics, pulmonary vascular remodeling, inflammation, and fibrosis, to a similar or greater extent than the PAH SOCs tested. In the PAB model, NTP42:KVA4 improved RV geometries and contractility, normalized RV stiffness, and significantly increased RV ejection fraction. In both models, NTP42:KVA4 promoted beneficial RV adaptation, decreasing cellular hypertrophy, and increasing vascularization. Notably, elevated expression of the TP target was observed both in RV tissue from these and related disease models, and in clinical RV specimens of PAH and DCM. Conclusion This study shows that, through antagonism of TP signaling, NTP42:KVA4 attenuates experimental PAH pathophysiology, not only alleviating pulmonary pathologies but also reducing RV remodeling, promoting beneficial hypertrophy, and improving cardiac function. The findings suggest a direct cardioprotective effect for NTP42:KVA4, and its potential to be a disease-modifying therapy in PAH and other cardiac conditions.